2018
DOI: 10.1016/j.bjps.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of patient satisfaction (using the BREAST-Q questionnaire) with bilateral breast reconstruction following risk-reducing or therapeutic mastectomy

Abstract: This study highlights the need for clinicians to take into account the indication for surgery as a major psychological factor in patients' perception of self and experience of surgery. It demonstrates that bilateral immediate reconstruction patients report similar physical symptoms irrespective of indication for mastectomy, but the decision-making process in terms of risk-balancing and diagnosis influences satisfaction with self and surgery. It underlines the importance of preoperative management of expectatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Studies demonstrated that worse overall health status among survivors negatively influences satisfaction with breast reconstruction [ 40 ]. Therefore, it is conclusive that previvors had a significantly higher satisfaction in psychosocial well-being, sexual well-being, and physical well-being (chest) compared to survivors and is in accordance with previous data [ 41 ]. One might have expected otherwise while therapeutic mastectomies are accepted as a core component of cancer treatment and CRRM is in context with the cancer-affected breast surgery and therefore could be considered unavoidable.…”
Section: Discussionsupporting
confidence: 92%
“…Studies demonstrated that worse overall health status among survivors negatively influences satisfaction with breast reconstruction [ 40 ]. Therefore, it is conclusive that previvors had a significantly higher satisfaction in psychosocial well-being, sexual well-being, and physical well-being (chest) compared to survivors and is in accordance with previous data [ 41 ]. One might have expected otherwise while therapeutic mastectomies are accepted as a core component of cancer treatment and CRRM is in context with the cancer-affected breast surgery and therefore could be considered unavoidable.…”
Section: Discussionsupporting
confidence: 92%
“…In five studies satisfying our inclusion criteria, but with limited information or missing data, we contacted the authors with additional questions or a request to provide us with the missing or additional data. [15][16][17][18][19] Otherwise, we used the data of three studies [15][16][17] as presented and discussed possible consequences of missing data. Two studies were excluded because the missing data could not be retrieved.…”
Section: Data Extraction and Risk-of-bias Assessmentmentioning
confidence: 99%
“…Patient satisfaction with mastectomy and immediate reconstruction is shown to differ between those undergoing therapeutic mastectomy due to cancer as opposed to unaffected women with BRCA mutation having RRM. Physical well-being is the same but psychosocial and sexual well-being was lower in unaffected BRCA mutation carriers [ 73 ].
Indicators for a patient to be likely of having a genetic mutation linked to breast cancer.
…”
Section: Who Should We Test For Brca Mutation and At What Time?mentioning
confidence: 99%